(3QDjI eNJdaIs - (3MGeO MehO(B, (3GdYLdGfs ((3HjQhJ(B:s (3eQcR OQGSGJ GdhMOI GdYQHjI(B,s, 2010)
(3Gdbje GdOjfjI hGdNjGQ GdEbJUGOj(B- (3GdQHG, hGdaGFOI hGdOjf(B- (3GdQHG hGdebJVjGJ GdEbJUGOjI(B- (3GdEbJUGO GdESdGej heVGejfg GdCNdGbjI(B- (3GdUfGYI GdeUQajI GdESdGejI(B- (3GddLGf GdETQGajI heCRb GdELJgGO(B- (3JfXje GdUfGYI GdeUQajI GdESdGejI(B- (3eSJbHd GdUfGYI GdeUQajI GdESdGejI aj GdchjJs
(3GdedGMb U(B.267(3; cTGa eUWdMGJ U(B275(3; GdeQGLY U(B.281s
Keywords: (3GdEbJUGO GdESdGejs; (3GdJehjd GdESdGejs; (3GdQHGs